Health-related stigma among Indigenous Peoples in Canada: A scoping review - Liam Rourke; Ronald Damant; Janice Y. Kung; Chantell Widney (PLoS ONE, 2025)
Background Indigenous communities in Canada are disproportionately affected by health conditions linked to stigma, warranting the attention of researchers seeking to understand this culturally-determined phenomenon. This study explores the scope of research on health-related stigma conducted with the First Nations, Inuit, and Métis Peoples. Method We conducted a scoping review using the method described by Arksey and O’Malley. We searched health and social science databases from 1963 to present using the subject headings Stigma and Health delimited by terms indexing over 600 Indigenous groups in Canada. Within the 1,852 results, we searched for reports in which the construct stigma was used to describe some facet of the participants’ experience of a health condition. We excluded studies in which stigma derived from the participants’ sexual orientation, occupation, or cultural identity. We extracted information about the participants’ health condition, Indigenous affiliation, forms of stigma experienced, and their responses. Results 25 studies involving 1,187 participants met our inclusion criteria. Inuit, First Nation, and Métis participants were drawn from communities in Alberta, British Columbia, Manitoba, Nunavut, Ontario, Quebec, and Saskatchewan. Stigma was reported by people living with HIV, mental health concerns, tuberculosis, STIs, type 2 diabetes, arthritis, physical disabilities, asthma, arthritis, substance use disorders, and FASD. Most frequently they reported enacted stigma expressed as social and physical distancing by perpetrators who interpret the diagnoses and symptoms as marks of social deviance or disease contagion. The primary response to stigma was to conceal one’s condition in ways that increased the disease burden. Interpretation Canada’s Indigenous communities have escaped the attention, or perhaps interest, of researchers investigating health-related stigma. In five decades of research, the subject surfaces only tangentially in reports designed to explore other aspects of their health. In the absence of research, pressing questions remain, some about stigma as a construct of social science and some about the health of Indigenous Peoples in Canada.